Electroluminescent organic polymer material as well as preparation method and application thereof

By condensing -tetrakis(4-carboxyphenyl)porphine (Tccp) and tetrakis(4-aminobenzene)ethylene (Tpe), and coordinate zinc ions to form an electroluminescent organic polymer material PVP-Zn-Tccp -Tpe, solves the problem of luminescence poor caused by Tccp due to induced aggregation quenching, and achieves the effect of significantly improving luminescence performance and stability.

CN119390969AActive Publication Date: 2025-02-07GUANGXI UNIV FOR NATITIES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411488646.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-07
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The luminescence poor problem caused by the induction of aggregation quenching phenomenon in the middle-tetrakis(4-carboxyphenyl)porphine (Tccp) is also problematic, and its luminescence performance is limited when used alone.

Method used

By condensing Tccp with tetra-(4-aminobenzene)ethylene (Tpe) and successfully coordinate zinc ions, the electroluminescent organic polymer material PVP-Zn-Tccp-Tpe is formed. This material forms acyl chloride groups through the action of dichloride sulfoxide, which enhances the connection between zinc porphyrin and tetrastyrene, and tritylene adjusts the lattice spacing to reduce the aggregation of the material.

Benefits of technology

The electrochemiluminescence intensity and stability are significantly improved. Compared with Tccp alone, its luminescence performance is significantly improved, and it has stronger conductivity and better electrochemiluminescence signals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390969A_ABST
    Figure CN119390969A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemiluminescence materials, and particularly relates to an electroluminescent organic polymer material and a preparation method and application thereof.The preparation method comprises the steps that 1, meso-tetra (4-carboxyphenyl) porphin and zinc salt are dissolved in a solvent to obtain a mixed system, and stirring reaction, centrifugation and drying are conducted to obtain a zinc porphyrin ligand; 2) respectively adding tetra-(4-aminobenzene) ethylene, thionyl chloride and mesitylene into the synthesized zinc porphyrin ligand, and uniformly stirring to obtain a secondary mixed system; the invention relates to a preparation method of a PVP-Zn-Tccp-Tpe organic polymer, which comprises the following steps of 1, adding a secondary mixed system into the PVP-Zn-Tccp-Tpe organic polymer, 3, adding polyvinylpyrrolidone into the secondary mixed system, and carrying out a heating reflux reaction at 70-80 DEG C for 20-25 h, and 4, carrying out centrifugal washing and drying after the reaction to obtain the PVP-Zn-Tccp-Tpe organic polymer. Compared with a Zn-Tccp-Tpe polymer and a PVP-Tccp-Tpe polymer, the PVP-Zn-Tccp-Tpe organic polymer has stronger electrochemiluminescence signals and more stable luminescence performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemiluminescence (ECL) materials, and in particular to an electroluminescent organic polymer material and a preparation method and application thereof. Background Art

[0002] The electrochemiluminescence process is a radiation process, which refers to the highly active free radicals generated by the material near the working electrode participating in the electron transfer process, thereby forming an excited state. When returning to the ground state, the excess energy is released in the form of light. Because it does not require an additional light source, it can effectively reduce the impact of background signals. In addition, its wide detection range has attracted widespread attention.

[0003] Due to their unique molecular structure and electronic properties, porphyrin derivatives usually have a large planar structure, good electron transfer ability and light absorption characteristics. At the same time, in terms of electroluminescence, porphyrin derivatives can change their luminescent color or improve their luminescence efficiency by changing their structure, such as changing their substituents, bridging groups or core coordinated metal ions; at the same time, porphyrin derivatives usually have a high electrode transfer efficiency, and their electron conduction rate is further improved by coordinating different metal ions at the porphyrin center, making it more conducive to the transfer of electrons from the cathode to the luminescent layer, thereby improving their luminescence efficiency; finally, compared with other organic substances, porphyrin is widely present in animals and plants in nature, and is an environmentally friendly substance. By designing and synthesizing porphyrin derivatives with good stability, the life and stability of the sensor can be effectively improved. However, porphyrin and its derivatives will form aggregates in aqueous solution or solid, resulting in emission quenching, which is still a huge challenge for porphyrin and its derivatives.

[0004] Tetrakis-(4-aminophenyl)ethylene (Tpe) is a compound with unique optical properties. It usually does not emit light in solution, but can emit strong fluorescence when aggregated, a phenomenon known as aggregation-induced emission (AIE). Summary of the invention

[0005] In view of the above problems, the present invention provides an electroluminescent organic polymer material and a preparation method and application thereof. The electroluminescent organic polymer material solves the problem of poor luminescence caused by the induced aggregation quenching phenomenon of tetrakis(4-carboxyphenyl)porphine (Tccp) itself; at the same time, the condensation of Tpe and Tccp has significantly improved the luminescence performance compared with the use of Tccp alone, and the successful coordination of zinc ions further improves the conductivity of the polymer and enhances its luminescence performance.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing an electroluminescent organic polymer material comprises the following steps:

[0008] (1) dissolving equal moles of tetrakis(4-carboxyphenyl)porphine (Tccp) and zinc salt in a solvent to obtain a mixed system, stirring the mixture at room temperature, centrifuging, and drying to obtain a zinc porphyrin (Zn-Tccp) ligand;

[0009] (2) adding tetrakis-(4-aminophenyl)ethylene (Tpe) and dichlorothionyl to the Zn-Tccp ligand synthesized in step (1), respectively, stirring evenly, to obtain a secondary mixing system;

[0010] (3) adding polyvinyl pyrrolidone (PVP) to the secondary mixed system obtained in step (2), and heating under reflux at 70-80° C. for 20-25 h;

[0011] (4) The solution obtained after the reaction is centrifuged, washed, and dried to obtain the electroluminescent organic polymer material (PVP-Zn-Tccp-Tpe).

[0012] Preferably, the zinc salt in step (1) is one or more of zinc acetate, zinc nitrate, zinc sulfate or zinc chloride, and the solvent is anhydrous ethanol or methanol.

[0013] Preferably, the concentrations of meso-tetrakis(4-carboxyphenyl)porphine and zinc salt in step (1) are both 0.5-2.0 nmol / mL.

[0014] Preferably, the stirring time in step (1) is 2-6 hours, and the centrifugal conditions are a rotation speed of 6000-10000 rpm and a time of 5-15 min.

[0015] Preferably, the mass ratio of tetrakis-(4-aminophenyl)ethylene to meso-tetrakis(4-carboxyphenyl)porphine is 1:1, and the dosage ratio of thionyl chloride to meso-tetrakis(4-carboxyphenyl)porphine is 3 mL:2 mg.

[0016] Preferably, the preparation method further comprises adding mesitylene in step (2), and the dosage ratio of mesitylene to dichloride is 1:1.

[0017] Preferably, the concentration of Zn-Tccp in the secondary mixing system of step (2) is 0.2-0.6 nmol / mL, and the concentration of tetrakis-(4-aminophenyl)ethylene is 0.4-1.2 nmol / mL.

[0018] Preferably, the mass ratio of polyvinyl pyrrolidone to meso-tetrakis(4-carboxyphenyl)porphine in step (3) is 5:1.

[0019] The present invention also provides an electroluminescent organic polymer material prepared according to the above method.

[0020] In addition, the present invention also provides an application of the electroluminescent organic polymer material prepared according to the above-mentioned preparation method in an electrochemiluminescent sensor.

[0021] By adopting the above technical solution, the beneficial effects of the present invention are:

[0022] The PVP-Zn-Tccp-Tpe electroluminescent organic polymer material obtained by the present invention solves the problem of poor luminescence caused by the induced aggregation quenching phenomenon of Tccp itself; at the same time, the condensation of Tpe and Tccp, compared with the use of Tccp alone, its luminescent performance has been significantly improved, and the successful coordination of zinc ions further improves the conductivity of the polymer and improves its luminescent performance. In addition, thionyl chloride, as a solvent, can also react with the carboxyl group of the zinc porphyrin ligand to produce an acyl chloride group at the same time, and the acyl chloride group is more likely to react with the amino group of tetraphenylethylene, so that the two ligands of zinc porphyrin and tetraphenylethylene are effectively connected; mesitylene can adjust the lattice spacing, reduce the degree of aggregation of the material, thereby further improving the luminescent intensity. Therefore, the PVP-Zn-Tccp-Tpe electroluminescent organic polymer material obtained by the present invention has a significantly improved electrochemiluminescence intensity compared with its various ligands (Tccp, Tpe, Zn-Tccp). Moreover, the organic polymer (PVP-Zn-Tccp-Tpe) of the present invention has a stronger and more excellent electrochemiluminescent signal and a more stable luminescent performance compared with the Zn-Tccp-Tpe polymer material and the PVP-Tccp-Tpe polymer material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention provides a synthesis route for an electroluminescent organic polymer material.

[0024] Figure 2 These are SEM images of the materials obtained in Example 1 and Comparative Example 1 of the present invention, wherein A and B are SEM images of the material obtained in Comparative Example 1 at 200nm and 100nm; C and D are SEM images of the material obtained in Example 1 at 1μm and 300nm.

[0025] Figure 3 These are the XRD diagrams of the three organic polymer materials Zn-Tccp-Tpe, PVP-Tccp-Tpe and PVP-Zn-Tccp-Tpe in the present invention.

[0026] Figure 4 This is the ultraviolet absorption diagram of the electroluminescent organic polymer material obtained in Example 1 of the present invention.

[0027] Figure 5 This is the Fourier transform infrared spectrum of the electroluminescent organic polymer material obtained in Example 1 of the present invention.

[0028] Figure 6 This is an X-ray photoelectron spectrometer analysis spectrum of the electroluminescent organic polymer material obtained in Example 1 of the present invention.

[0029] Figure 7 This is the ECL emission wavelength spectrum of the electroluminescent organic polymer material obtained in Example 1 of the present invention.

[0030] Figure 8 This is a comparison chart of ECL signals of the electroluminescent organic polymer materials obtained in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention under the same conditions.

[0031] Fig. 9 It is a comparison diagram of the ECL signals of Example 1 of the present invention and various ligands.

[0032] Fig.10 It is a comparison chart of the CV responses of Example 1 of the present invention and various ligands.

[0033] Fig.11 This is a comparison chart of the CV responses of the electroluminescent organic polymer materials obtained in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] A method for preparing an electroluminescent organic polymer material (PVP-Zn-Tccp-Tpe), comprising the following steps:

[0037] (1) dissolving 10 mg of tetrakis(4-carboxyphenyl)porphine (Tccp) and 3 mg of zinc acetate in an anhydrous ethanol solvent in a round-bottom flask to obtain a mixed system with a Tccp and zinc acetate concentration of 0.83 nmol / mL, stirring at room temperature for 4 hours, centrifuging at a speed of 10,000 rpm for 5 minutes, and drying at 37° C. to obtain a zinc porphyrin Zn-Tccp ligand;

[0038] (2) adding 10 mg of tetrakis-(4-aminophenyl)ethylene (Tpe), 15 mL of dichlorothionyl and 15 mL of 1,3,5-trimethylbenzene to the Zn-Tccp ligand synthesized in step (1), respectively, and stirring evenly to obtain a secondary mixed system with a Zn-Tccp concentration of 0.415 nmol / mL and a Tpe concentration of 0.83 nmol / mL;

[0039] (3) adding 50 mg of polyvinyl pyrrolidone (PVP) to the secondary mixed system obtained in step (2), and heating under reflux at 78° C. for 24 h;

[0040] (4) The solution obtained after the reaction was centrifuged and washed at a speed of 10,000 rpm for 5 min. The washing reagents were tetrahydrofuran and methanol. The two reagents were used for washing alternately for a total of six times. The solution was then dried at 37° C. in vacuum to obtain the electroluminescent organic polymer material (PVP-Zn-Tccp-Tpe).

[0041] Example 2

[0042] A method for preparing an electroluminescent organic polymer material (PVP-Zn-Tccp-Tpe), comprising the following steps:

[0043] (1) dissolving 10 mg of meso-tetrakis(4-carboxyphenyl)porphine (Tccp) and 3 mg of zinc nitrate in a methanol solvent in a round-bottom flask to obtain a mixed system with a Tccp and zinc acetate concentration of 0.12 nmol / mL, stirring at room temperature for 4 hours, centrifuging at a speed of 10,000 rpm for 5 minutes, and drying at 37° C. to obtain a zinc porphyrin Zn-Tccp ligand;

[0044] (2) adding 10 mg of tetrakis-(4-aminophenyl)ethylene (Tpe), 15 mL of dichlorothionyl and 15 mL of 1,3,5-trimethylbenzene to the Zn-Tccp ligand synthesized in step (1), respectively, and stirring evenly to obtain a secondary mixed system with a Zn-Tccp concentration of 0.415 nmol / mL and a Tpe concentration of 0.83 nmol / mL;

[0045] (3) adding 50 mg of polyvinyl pyrrolidone (PVP) to the secondary mixed system obtained in step (2), and heating under reflux at 80° C. for 24 h;

[0046] (4) The solution obtained after the reaction was centrifuged and washed at a speed of 10,000 rpm for 5 min. The washing reagents were tetrahydrofuran and methanol. The two reagents were used for washing alternately for a total of six times. The solution was then dried at 37° C. in vacuum to obtain the electroluminescent organic polymer material (PVP-Zn-Tccp-Tpe).

[0047] Comparative Example 1

[0048] A method for preparing an electroluminescent organic polymer material (Zn-Tccp-Tpe), comprising the following steps:

[0049] (1) dissolving 10 mg of tetrakis(4-carboxyphenyl)porphine (Tccp) and 3 mg of zinc acetate in anhydrous ethanol solvent to obtain a mixed system with a Tccp and zinc acetate concentration of 0.83 nmol / mL, stirring at room temperature for 4 hours, centrifuging at a speed of 10,000 rpm for 5 minutes, and drying at 37° C. to obtain a zinc porphyrin Zn-Tccp ligand;

[0050] (2) adding 10 mg of tetrakis-(4-aminophenyl)ethylene (Tpe), 15 mL of dichlorothionyl and 15 mL of 1,3,5-trimethylbenzene to the Zn-Tccp ligand synthesized in step (1), stirring evenly to obtain a secondary mixed system with a Zn-Tccp concentration of 0.415 nmol / mL and a Tpe concentration of 0.83 nmol / mL; heating under reflux at 78° C. for 24 h;

[0051] (3) The solution obtained after the reaction is centrifuged and washed at a speed of 10,000 rpm for 5 min. The washing reagents are tetrahydrofuran and methanol. The two reagents are used for washing alternately for a total of six times. The solution is then dried at 37° C. in vacuum to obtain the electroluminescent organic polymer material (Zn-Tccp-Tpe).

[0052] Comparative Example 2

[0053] A method for preparing an electroluminescent organic polymer material (PVP-Tccp-Tpe), comprising the following steps:

[0054] (1) 10 mg of tetrakis-(4-aminophenyl)ethylene (Tpe), 15 mL of dichlorothionyl and 15 mL of 1,3,5-trimethylbenzene were added to the Tccp ligand respectively, and stirred evenly to obtain a mixed system with a Zn-Tccp concentration of 0.415 nmol / mL and a Tpe concentration of 0.83 nmol / mL;

[0055] (2) adding 50 mg of polyvinyl pyrrolidone (PVP) to the mixed system obtained in step (1), and heating under reflux at 78° C. for 24 h;

[0056] (3) The solution obtained after the reaction is centrifuged and washed at a speed of 10,000 rpm for 5 min. The washing reagents are tetrahydrofuran and methanol. The two reagents are used for washing alternately for a total of six times. The solution is then dried at 37° C. in vacuum to obtain the electroluminescent organic polymer material (PVP-Tccp-Tpe).

[0057] The electrochemiluminescent organic polymer materials obtained in Example 1, Comparative Example 1 and Comparative Example 2 were characterized by SEM and XRD. The results were as follows: Figure 2 And like 3. Depend on Figure 2 The SEM characterization of A and B shows that the organic polymer material (Zn-Tccp-Tpe) obtained in Comparative Example 1 presents a layered stacking structure, but its flaky particles are relatively large. Figure 2 From the SEM characterization of C and D, it can be seen that after adding PVP, the diameter of the flaky particles of the organic polymer material (PVP-Zn-Tccp-Tpe) obtained in Example 1 is smaller than that of the organic polymer material in Comparative Example 1.

[0058] Depend on Figure 3 From the XRD characterization, it can be seen that the organic polymer material (PVP-Zn-Tccp-Tpe) obtained in Example 1 has an obvious characteristic peak at 0.98°. The organic polymer material (Zn-Tccp-Tpe) obtained in Comparative Example 1 has an obvious characteristic peak at 1.14°. The organic polymer material (PVP-Tccp-Tpe) obtained in Comparative Example 2 has an obvious peak at 0.96°.

[0059] The present invention also carried out UV-Vis, FT-IR, XPS characterization and ECL test on the electrochemiluminescent organic polymer material obtained in Example 1. The results are shown in Figures 4 to 7 shown.

[0060] Depend on Figure 4 Characterization by UV-visible spectrophotometer shows that the absorption wavelength of the organic polymer material obtained in Example 1 is 273 nm.

[0061] Depend on Figure 5 It can be seen that the vibration peak of the C=O bond of Tccp was observed at 1700cm-1 by Fourier infrared transform spectroscopy, and the vibration peak of the CO bond was observed at 3356cm-1, indicating that the Tccp surface carries -COOH. The vibration peaks of the NH bond of Tpe were observed at 1520cm-1, 1620cm-1, and 3360cm-1, indicating that the Tpe surface carries -NH2. In the infrared test of PVP, the broad and strong absorption peaks at 3090cm-1 to 3680cm-1 are produced by the stretching vibration of the CN bond, and the peak at 1670cm-1 is produced by the stretching vibration of C=O. The infrared spectrum of PVP-Zn-Tccp-Tpe only retains the peak at 1670cm-1 compared with Tccp and Tpe, but this peak may also be the vibration peak produced by PVP, so this peak may be the amide bond formed by the condensation of Tccp and Tpe, or it may be the vibration peak produced by the carbonyl group on PVP.

[0062] Depend on Figure 6 It can be seen that the X-ray photoelectron spectroscopy (XPS) technique characterization obtained a C=C peak at 284.18 eV, a CO peak at 531.68 eV, a C=O peak at 532.98 eV, and a -C=O peak at 288.08 eV. Figure 1 The polymer structure and Figure 5 From the infrared spectrum, it is judged that the peak at 288.08 eV is due to the vibration of the amide bond, and the Zn-N peak at 1021.7 eV is obtained.

[0063] Depend on Figure 7 It can be seen that after performing ECL testing using different wavelength filters (within the range of 480-640 nm, each filter wavelength interval is 20 nm), the ECL emission spectrum of the organic polymer material of Example 1 is obtained by data fitting, and its ECL maximum emission wavelength is 538 nm.

[0064] Application Example 1

[0065] The present invention uses Example 1 to compare the electrochemiluminescence intensity of the organic polymer materials prepared in Example 1, Comparative Example 1 and Comparative Example 2. The specific operation steps are as follows:

[0066] (1) Take a glassy carbon electrode, polish it with aluminum powder, then ultrasonically clean it with distilled water and ethanol in turn, and blow dry it with nitrogen.

[0067] (2) Take 1 mg of the organic polymers of Example 1, Comparative Example 1 and Comparative Example 2 respectively, and disperse them in 6 mL of 1% chitosan solution. Take 10 μL of the dispersion and drop it on the surface of the glassy carbon electrode, let it stand at room temperature to dry as the working electrode. Prepare 0.1 M PBS (pH = 7.4) containing 0.1 M K2S2O8 as a co-reaction solvent. A saturated Ag / AgCl electrode is used as a reference electrode, and a platinum wire electrode is used as a counter electrode to construct a three-electrode system with the working electrode prepared above. The three-electrode system is placed in a co-reaction solvent, and the ECL signal is tested by cyclic voltammetry.

[0068] The results are as follows Figure 8 As shown, the electrochemiluminescence signal of the organic polymer (PVP-Zn-Tccp-Tpe) of Example 1 is excellent and the luminescence stability is good; the electrochemiluminescence signal of the organic polymer (Zn-Tccp-Tpe) of Comparative Example 1 is low and the stability is poor; the electrochemiluminescence signal of the organic polymer (PVP-Tccp-Tpe) of Comparative Example 2 is stable, but the signal intensity is not as good as that of the organic polymer of Example 1.

[0069] Application Example 2

[0070] In Application Example 2 of the present invention, the method of Application Example 1 was used to prepare working electrodes with Tccp, Tpe, Zn-Tccp and PVP-Zn-Tccp-Tpe, respectively. The same method as in Application Example 1 was used to test the ECL curves and CV curves of the working electrodes and the working electrodes in Experimental Example 1, respectively. The results are as follows: Fig. 9 , 10 shown.

[0071] Depend on Fig. 9 From the ECL results, it can be seen that the ECL intensity of PVP-Zn-Tccp-Tpe in Example 1 is significantly improved compared with its other ligands.

[0072] Depend on Fig.10 From the CV results, it can be seen that the reduction peak voltage of the organic polymer in Example 1 is shifted to the left compared with the reduction peak voltages of its ligands, indicating that the organic polymer material is easier to absorb electrons and more likely to undergo reduction reactions, and then its electrons are more likely to transition and return to the ground state to radiate light, which corresponds to its ECL test results.

[0073] Application Example 3

[0074] In Application Example 3 of the present invention, the method of Application Example 1 was used to prepare working electrodes with PVP-Tccp-Tpe, Zn-Tccp-Tpe and PVP-Zn-Tccp-Tpe, respectively. The same method as in Application Example 1 was used to test the CV curve signals of the working electrodes prepared from the above three organic polymer materials. The results are as follows: Fig.11 shown.

[0075] like Fig.11 As shown in the CV test, the reduction potential of PVP-Zn-Tccp-Tpe is the lowest, at about -1.5V, indicating that compared with the three materials, PVP-Zn-Tccp-Tpe is more likely to undergo a reduction reaction, so its electrode is more likely to accept energy and enter an excited state. On the other hand, this material has better electroluminescence performance than the other two materials. This result is also consistent with Figure 8 The ECL results correspond to the

[0076] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.

Claims

1. A method for preparing an electroluminescent organic polymer material, characterized in that: The steps include: (1) dissolving equal moles of meso-tetrakis(4-carboxyphenyl)porphine and zinc salt in a solvent to obtain a mixed system, stirring the mixture for reaction, centrifuging the mixture, and drying the mixture to obtain a zinc porphyrin ligand; (2) adding tetrakis-(4-aminophenyl)ethylene and dichlorothionyl to the zinc porphyrin ligand synthesized in step (1), respectively, stirring evenly, and obtaining a secondary mixing system; (3) adding polyvinyl pyrrolidone to the secondary mixed system obtained in step (2), and heating under reflux at 70-80°C for 20-25 hours; (4) The solution obtained after the reaction is centrifuged, washed, and dried to obtain the electroluminescent organic polymer material.

2. The method for preparing an electroluminescent organic polymer material according to claim 1, characterized in that: In step (1), the zinc salt is one or more of zinc acetate, zinc nitrate, zinc sulfate or zinc chloride, and the solvent is anhydrous ethanol or methanol.

3. The method for preparing an electroluminescent organic polymer material according to claim 1, characterized in that: The concentrations of meso-tetrakis(4-carboxyphenyl)porphine and zinc salt in step (1) are both 0.5-2.0 nmol / mL.

4. The method for preparing an electroluminescent organic polymer material according to claim 1, characterized in that: The stirring time in step (1) is 2-6 hours, and the centrifugal conditions are a rotation speed of 6000-10000 rpm and a time of 5-15 min.

5. The method for preparing an electroluminescent organic polymer material according to claim 1, characterized in that: The mass ratio of the tetrakis-(4-aminophenyl)ethylene to meso-tetrakis(4-carboxyphenyl)porphine is 1:1, and the dosage ratio of the dichlorothionyl to meso-tetrakis(4-carboxyphenyl)porphine is 3 mL:2 mg.

6. The method for preparing an electroluminescent organic polymer material according to claim 1, characterized in that: The method further comprises adding mesitylene in step (2), wherein the ratio of mesitylene to dichlorothionyl is 1:

1.

7. The method for preparing an electroluminescent organic polymer material according to claim 6, characterized in that: In step (2), the concentration of zinc porphyrin in the secondary mixing system is 0.2-0.6 nmol / mL, and the concentration of tetrakis-(4-aminophenyl)ethylene is 0.4-1.2 nmol / mL.

8. The method for preparing an electroluminescent organic polymer material according to claim 1, characterized in that: The mass ratio of polyvinyl pyrrolidone to meso-tetrakis(4-carboxyphenyl)porphine in step (3) is 5:

1.

9. An electroluminescent organic polymer material prepared by the method according to any one of claims 1 to 8.

10. Use of the electroluminescent organic polymer material prepared by the preparation method according to any one of claims 1 to 8 in an electrochemiluminescence sensor.

Citation Information

Patent Citations

  • Compound, photosensitive combination, solidified combination, solidified combination for filter, color filter and manufacturing method thereof

    CN101093355A

  • Preparation method of H-MOF-5 / TCPP fluorescent composite material

    CN109438456A

  • Application of multi-benzene-ring conjugated molecule in preparation of antiviral drug and antiviral drug

    CN113101283A

  • Preparation method of tetra-p-aminophenyl zinc porphyrin-AIE-based MOF fluorescent fiber capable of being used for counterfeiting prevention

    CN114892305A

  • Preparation method of crystalline two-dimensional film

    CN118290682A